Advancing CCU Technologies Pursuant to the SDGs: A Challenge for Policy Making - Olfe-Kräutlein, Barbara (Frontiers in Energy Research, 2020)
The implementation of the United Nations Sustainable Development Goals (SDGs) is indispensable for building a sustainable and just future for all humans and our planet. The SDGs are global goals. However, their implementation equally calls for action by a variety of actors in government, business, and civil society. Thus, policy making as well as industrial innovation efforts need to be designed to facilitate rather than hinder the implementation of the SDGs. Consequently, it is necessary to ensure that the possible environmental, economic, and societal impacts of technological innovations aiming for public support and funding in research, development, and market implementation are aligned with the respective objectives of the SDGs. Carbon capture and utilization (CCU) applications are an example of such innovations. By capturing and utilizing CO2, they are intended to have positive impacts on economy, society, and environment. Next to industries’ own efforts to advance such technologies, CCU is currently funded by governments in several countries, and such funding is likely to increase. Therefore, an assessment of the compatibility of CCU technologies with the SDGs is as much necessary as it is overdue. Hence, this paper elucidates on how CCU might contribute to or hinder the delivery of the SDGs. By comparing CCUs against the SDGs, it can be concluded that, under certain conditions, they might deliver contributions to several SDGs. The main contributions are expected within the context of energy transition processes, and in societal advancements that are linked to technological progress. For eight out of the seventeen SDGs, positive and indirect negative effects can be predicted. Therefore, the development and implementation of CCU aligned with the SDGs poses a challenge for policy makers when designing frameworks and funding schemes. Specific risks need to be monitored and considered in policy making. This paper therefore argues that the SDGs should be used as a framework for assessing potential societal effects of CCU technologies. The findings demonstrate that such an approach is necessary in order to identify and enhance the positive (and avoid indirect negative) effects that CCU technologies might have on people, prosperity and planet.